Whole-plant grain sorghum and inoculated corn silages in mid-lactation dairy cow diets - K.K. Bolsen; John E. Shirley; A. Laytimi; J. Dickerson (Kansas Agricultural Experiment Station Research Reports, 1989)
Whole-plant grain sorghum silage and Silo-Best-Soluble inoculated and uninoculated control corn silages were compared in complete-mixed diets for mid-lactation dairy cows. Cows fed the inoculated corn silage yielded .6 lb and those fed the grain sorghum silage yielded 1.7 lb more fat-corrected milk than those fed the control corn silage. Fat percentage for the cows fed the grain sorghum silage was .2 units greater than for those fed the control and the inoculated corn silages. Similar percentages were obtained for milk protein and solids-not-fat. Cows fed the inoculated corn silage had the highest weight gain (+150 lb), those fed the control corn silage had intermediate gains (+132 lb), and those fed the grain sorghum silage had the lowest gains (+106 lb). We conclude that dairy farmers can derive positive responses from inoculation of corn silage and that grain sorghum silage can be substituted for corn silage in mid-lactation dairy cow diets.; Dairy Day, 1989, Kansas State University, Manhattan, KS, 1989; The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy Day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-140-S; Report of progress (Kansas Agricultural Experiment Station); 580; Dairy; Grain sorghum; Corn silage; Lactation